Therapeutic effectiveness of ultrasound-guided percutaneous balloon dilatation for arteriovenous internal fistula stenosis - ZENG Min; YANG Ding-ping; ZHENG Ting (Linchuang shenzangbing zazhi)
Objective To explore and compare the efficacy of ultrasound-guided percutaneous balloon dilatation and surgical treatment for arteriovenous stenosis with thrombosis. Methods The clinical data of 72 patients with arteriovenous internal fistula stenosis treated by our center from December2013 to June 2017 were retrospectively analyzed,among which 38 were treated with balloon dilatation and 34 were treated with surgical repair. Results The general data of the two groups showed statistically significant differences in gender and smoking history( P < 0. 05),while the remaining data and internal fistula characteristics showed no significant differences( P > 0. 05). After 6 and 12 months of followup,the patency rate of internal fistula was significantly higher in the balloon group than in the surgery group( P < 0. 05). The incidence of postoperative hemorrhage in the balloon group was significantly lower,and the mean survival time was significantly longer than those in the surgery group( P < 0. 05). The72 patients were followed up to May 30,2018,and the survival time of the patients in the balloon group was significantly longer than that in the surgery group( P < 0. 05). Conclusions The postoperative patency rate of ultrasound-guided balloon dilatation for the treatment of arteriovenous internal fistula stenosis and thrombosis is higher than that of the surgery group,which can strive for a longer survival time for patients.